Implementation of Fuzzy Linear Programming (FLP) on Optimizing the Production of Vegetable Rice and Lontong in Warung Makan Ibu Eni - Herianto, Tulus Joseph; Feren; Nurhalimah, Aisyah; Br. Sembiring, Melisa M.; Sembiring, James P. (Talenta Publisher, 2023)
Sellers of vegetable rice and lontong want to increase production levels, but are hampered by determining the quantity of ingredients and the time to produce them. This research aims to optimize the production of vegetable rice and lontong using Fuzzy Linear Programming-Right Hand Side (FLP-RHS) by considering uncertainty in demand, raw material prices and production time. It is hoped that the research results can help sellers determine optimal production quantities. The research was conducted at Warung Makan Ibu Eni which is located on Jalan Sekip Gang Suropati, Medan Petisah District, Medan City, Indonesia. Data was obtained through direct interviews with the owner of Ibu Eni's food stall to obtain information regarding production time, raw material supplies, selling prices and daily production. Data is processed using FLP and using the POM-QM application. In order to obtain maximum profit, namely Rp. 812,070, 37.93 packs of vegetable rice must be produced and 52.3 packs of lontong must be produced.